New Euthygramma (Insecta: Caloneurida) from the Kulchumovo Formation (Vyatkian Stage, Upper Permian) of Vyazovka (Orenburg Region of Russia) - Rasnitsyn, Alexandr P. (Zootaxa, 2025)
Euthygramma storozhenkoi Rasnitsyn, sp. nov. is described in the family Caloneuridae (order Caloneurodea) based on the unique fossil from the uppermost Permian Kulchumovo Fm. in the Orenburg Region of Russia. The new record is the latest for the family and for the entire order.